Human Dignity : Establishing Worth and Seeking Solutions - Sieh, Edward; McGregor, Judy (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book examines the concept of dignity from a variety of global perspectives. It scrutinizes how dignity informs policy and practice, and is influenced by international and domestic law, human rights values, and domestic politics. An exciting collection of essays, this edited volume provides an analysis of human rights as they are experienced by real people who have in many cases been forced to take action to further their own interests. Readers will discover an extensive range of issues discussed, from the internet, climate change and disabilities, to globalization, old-age, and migrants' rights. The last section deals with the impact of various issues on indigenous and migrant populations, specifically violence in Columbia, border issues in Tijuana, women's and children's rights violations, and the complex problems experienced by refugees, particularly in regards to citizenship. The interdisciplinary nature of this work makes it an invaluable read for scholars of Health Studies, Law, Human Rights, Sociology and Politics.- Resumé vydavatel